Critical Evaluation of the Charitable Trust as a Giving Device - Allan D. Vestal (Washington University Law Quarterly, 1957)
Thinking along traditional lines is misleading; charitable trusts have assumed a position of great significance in the examination and development of new social and economic concepts. For this reason, if for no other, a re-examination of the charitable trust is warranted.
Keywords: Charitable foundations; Charitable uses